2016
DOI: 10.1007/s11103-016-0563-7
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of miR158 causes pollen abortion in Brassica campestris ssp. chinensis

Abstract: We identified and cloned the two precursors of miR158 and its target gene in Brassica campestris ssp. chinensis, which both had high relative expression in the inflorescences. Further study revealed that over-expression of miR158 caused reduced pollen varbility, which was caused by the degradation of pollen contents from the binucleate microspore stage. These results first suggest the role of miR158 in pollen development of Brassica campestris ssp. chinensis. MicroRNAs (miRNAs) play crucial roles in many impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…MiR158 has been proven to regulate pollen development in non-heading Chinese cabbage ( Brassica campestris ssp. chinensis ) [72]. MiR159 and miR845 are involved in the control of stem length in rice [73] and crop resistance [74,75], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…MiR158 has been proven to regulate pollen development in non-heading Chinese cabbage ( Brassica campestris ssp. chinensis ) [72]. MiR159 and miR845 are involved in the control of stem length in rice [73] and crop resistance [74,75], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Abolished miR158 activity triggers PDP biogenesis following "two-hit, two-cleavage" model Earlier it was reported that miR158 targets a PPR and thereby regulates pollen development in Brassica campestris (Ma et al, 2017). However, our repeated attempts failed to identify the PPR as the target of miR158 in A. thaliana.…”
Section: Natural Variations In Mir158 Affect Pri-mir158 Processingmentioning
confidence: 89%
“…More recently it has been shown that miR158 play role in pollen development by regulating PPR in Brassica campestris (Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PPR-containing proteins constitute an important class of fertility restorer proteins that are required for generating a functional male gametophyte in CMS plants [ 14 , 19 ]. PPR-containing proteins have been previously confirmed as targets of miR158, miR161, miR475 and miR476 [ 69 , 78 , 79 ]. Here, miR5654 and miR1507 were also predicted to target PPR-containing proteins ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%